Perencanaan Produksi Agregat Pada Pabrik Tahu “Pak Tabah” - Almaash Putridewi; Santika Sari; Petrina Ziporah; Lukman Hakim; Hani Musyaffa Hadi; Kresna Putra Brata (JIE Scientific Journal on Research and Application of Industrial System, 2020)
Aggregate planning makes companies possible to arrange the way of optimally utilizing company resources in order to achieve effective and efficient capacity which is made based on future demand forecasts. Pak Tabah Tofu Factory is a home factory that produces White Tofu and Yellow Tofu. This factory is still operating traditionally without clear bookkeeping and planning. Demand forecasting and aggregate planning are made to predict the next period’s production by adjusting the number of workers so that the tofu production at the Pak Tabah Tofu Factory becomes more efficient. The selected method used by this research was selected trough the smallest MAPE score, named the Moving Average Method with a value of 0.136 and 0.11. In the aggregate planning, Mixed Strategy was chosen because this strategy produces the lowest production plan value of Rp, 554,526,200,- and Rp. 528,732,000,-. This strategy is the best strategy to be use by Pak Tabah’s Tofu Factory because not only produces for the delivery but also for the stock.